Efficient conversion of nitrogen to nitrogen-vacancy centers in diamond particles with high-temperature electron irradiation. (December 2020) - Mindarava, Yuliya; Blinder, Rémi; Laube, Christian; Knolle, Wolfgang; Abel, Bernd; Jentgens, Christian; Isoya, Junichi; Scheuer, Jochen; Lang, Johannes; Schwartz, Ilai; Naydenov, Boris; Jelezko, Fedor
Abstract: Fluorescent nanodiamonds containing negatively-charged nitrogen-vacancy (NV − ) centers are promising for a wide range of applications, such as for sensing, as fluorescence biomarkers, or to hyperpolarize nuclear spins. NV − centers are formed from substitutional nitrogen (P1 centers) defects and vacancies in the diamond lattice. Maximizing the concentration of NVs is most beneficial, which justifies the search for methods with a high yield of conversion from P1 to NV − . We report here the characterization of surface cleaned fluorescent micro- and nanodiamonds, obtained by irradiation of commercial diamond powder with high-energy (10 MeV) electrons and simultaneous annealing at 800 ∘ C. Using this technique and increasing the irradiation dose, we demonstrate the creation of NV − with up to 25% conversion yield. Finally, we monitor the creation of irradiation-induced spin-1 defects in microdiamond particles, which we associate with W16 and W33 centers, and investigate the effects of irradiation dose and particle size on the coherence time of NV − .